An alternative method to record rising temperatures during dental implant site preparation: a preliminary study using bovine bone - Domenica Laurito; Luca Lamazza; Girolamo Garreffa; Alberto De Biase (Istituto Superiore di Sanità, 2010)
Overheating is constantly mentioned as a risk factor for bone necrosis that could compromise the dental implant primary stability. Uncontrolled thermal injury can result in a fibrous tissue, interpositioned at the implant-bone interface, compromising the long-term prognosis. The methods used to record temperature rise include either direct recording by thermocouple instruments or indirect estimating by infrared thermography. This preliminary study was carried out using bovine bone and a different method of temperatures rising estimation is presented. Two different types of drills were tested using fluoroptic thermometer and the effectiveness of this alternative temperature recording method was evaluated.